Research progress of molecular typing and targeted therapy for triple-negative breast cancer - Xiang, Da lin; Yue, Xin (Frontiers in Oncology, 2025)
Triple-negative breast cancer (TNBC) is difficult to treat due to its high heterogeneity, strong invasiveness, high risk of recurrence and metastasis, and poor prognosis. Chemotherapy is still its main treatment, but limited by the lack of specific targets, drug resistance and other factors, the conventional efficacy is poor. In recent years, advances in genomics and other technologies have promoted the deepening of molecular typing studies and the development of targeted therapy for TNBC, providing a new direction for breaking through the therapeutic dilemma. Based on the biological characteristics of TNBC and the current treatment status, this article systematically reviews the latest progress of its molecular typing system, and discusses the breakthrough research results of targeted therapy strategies, aiming to provide a theoretical basis and practical reference for the precise treatment of TNBC.